
670×3.5+67×66-67简便方法?
14个回答
展开全部
=67*(10*3.5+66-1)
=67*(35+66-1)
=67*100
=6700
=67*(35+66-1)
=67*100
=6700
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
670×3.5+67×66-67
=67×35+67×66-67×1
=67×(35+66-1)
=67×100
=6700
=67×35+67×66-67×1
=67×(35+66-1)
=67×100
=6700
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
67x35+67x66-67x1
=67x(35+66-1)
=67x100
=670
=67x(35+66-1)
=67x100
=670
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
=67×35+67×66-67
=67×(35+66-1)
=67×100
=6700
=67×(35+66-1)
=67×100
=6700
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询